CONCEPTUAL MODEL OF MOBILE LEARNING APPLICATION FOR KINDERGARTEN CHILDREN - IBRAHIM, NORSHAHILA (2017)
Mobile Learning Application (MLA) refers to the use of mobile devices in delivering learning content using the advantages of mobile devices. Unfortunately, some drawbacks pertaining to such application have circumvented its use and purpose in classrooms.